New Terrorism - Gutteridge, William (Ed.) (London, 1986)
The New Terrorism brings together a number of important studies that have been published on the subject in recent years by the Institute for the Study of Conflict. Concentrating on Western Europe, the collection will help to meet the need for greater knowledge and understanding of terrorism at a time when Western governments are having to confront unpredictable and dangerous threats to security.
The institute for the study of conflict.
Keywords: Terrorism. 2. Terrorism- Europe